Nrf2 as a key player of redox regulation in cardiovascular diseases - Barančík, M; Grešová, L; Barteková, M; Dovinová, I (Physiological research, 2016)
The oxidative stress plays an important role in the development of cardiovascular diseases (CVD). In CVD progression an aberrant redox regulation was observed. In this regulation levels of reactive oxygen species (ROS) play an important role in cellular signaling, where Nrf2 is the key regulator of redox homeostasis. Keap1-Nrf2-ARE system regulates a great set of detoxificant and antioxidant enzymes in cells after ROS and electrophiles exposure. In this review we focus on radical-generating systems in cardiovascular system as well as on Nrf2 as a target against oxidative stress and a key player of redox regulation in cardiovascular diseases. We also summarize the current knowledge about the role of Nrf2 in pathophysiology of several CVD (hypertension, cardiac hypertrophy, cardiomyopathies) as well as in cardioprotection against myocardial ischemia/ reperfusion injury.
Keywords: kardiovaskulární nemoci; Animals; antioxidační responzivní elementy; Oxidative Stress; lidé; zvířata; NF-E2-Related Factor 2; oxidační stres; Cardiovascular Diseases; Antioxidant Response Elements; faktor 2 související s NF-E2; Humans